2015
DOI: 10.1007/s00520-015-2822-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single doses of IV palonosetron, up to 2.25 mg, on the QTc interval duration: a double-blind, randomized, parallel group study in healthy volunteers

Abstract: Purpose The use of serotonin type 3 (5-HT 3 ) receptor antagonists (RAs) in the prevention of nausea and vomiting caused by emetogenic chemotherapy is part of a comprehensive management strategy for patients undergoing chemotherapy. Electrocardiographic effects have been reported in patients after intravenous administration of 5-HT 3 RAs. The present study investigated the electrocardiogram (ECG) profile of the 5-HT 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A study by Morganroth et al included 221 healthy subjects who were assigned to receive one of the following five treatments: placebo, palonosetron (0.25, 0.75, or 2.25 mg), or moxifloxacin (400 mg) in order to study the effects of palonosetron on QTc interval ( 29 ). All three doses of palonosetron showed no significant effects on QTc prolongation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Morganroth et al included 221 healthy subjects who were assigned to receive one of the following five treatments: placebo, palonosetron (0.25, 0.75, or 2.25 mg), or moxifloxacin (400 mg) in order to study the effects of palonosetron on QTc interval ( 29 ). All three doses of palonosetron showed no significant effects on QTc prolongation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Morganroth et al included 221 healthy subjects who were assigned to receive one of the following five treatments: placebo, palonosetron (0.25, 0.75, or 2.25 mg), or moxifloxacin (400 mg) in order to study the effects of palonosetron on QTc interval ( 29 ). All three doses of palonosetron showed no significant effects on QTc prolongation ( 29 ). The main objective of the study was developed in accordance with the International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) E14 in order to analyze the potential of cardiovascular toxicity ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ondansetron for CINV prevention has been restricted to a maximum of 16 mg per dose [8]. The effect of palonosetron (PALO) on ECG measures has been studied in both healthy volunteers [9] and cancer patients [10][11][12]. Two of the trials found significant differences in heart rate (HR) after administration of PALO compared with baseline [10,12], but no HRcorrected cardiac measures significantly differed.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in several large randomised phase three trials, palonosetron is equally effective when compared to ondansetron [38], granisetron [39] and dolasetron [40] in preventing acute emesis and more effective in preventing delayed emesis. Importantly, QTc prolongation has not been described with palonosetron [41,42]. Updated antiemetic guidelines from the American Society of Clinical Oncology (ASCO) and the National Comprehensive Cancer Network (NCCN) recommend palonosetron as the preferred 5HT3 antagonist for patients who receive moderately emetogenic chemotherapy [43][44][45].…”
mentioning
confidence: 99%